MANAJEMEN STRATEGI PEMENANGAN CALON ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) PEREMPUAN DALAM PEMILIHAN UMUM KOTA SURABAYA TAHUN 2019 - Firdausi Nuzulla Isnainy; Trenda Aktiva Oktariyanda (Publika, 2022)
In the 2019 general election, there were as many as 34% of women's representation occupying the seats of the Surabaya City DPRD. However, of the 5 electoral districts in the City of Surabaya, the Surabaya electoral district 5 has the least representation of women elected, namely out of 10 members of the council elected there are only 1 female member, who comes from the PDI P. Seeing this, the purpose of this study is to analyze and describe the management strategy for the winning of female DPRD candidates in the 2019 Surabaya City general election (case study on PDI-P in electoral district 5, Surabaya City), with using the concept of strategic management according to Fred R. David (in Taufiqurokhman, 2016) which consists of 3 variables, namely strategy formulation, strategy implementation, and strategy evaluation. The type of research used is descriptive research with a qualitative approach. Meanwhile, the data collection technique is done through observation, interviews, and documentation. The data analysis techniques used in this study, namely data collection, data reduction, data display, and drawing conclusions/data verification. Based on the results of the research, there are several alternative strategies that have been successfully formulated and implemented by the candidates for legislative members, Bapillu and the DPC PDI-P Surabaya. However, there are also alternative strategies that are less than optimal in their implementation. So that, in the future mapping and recalculation of public votes is needed, as well as an analysis of the targeted electoral districts as part of the strategy in winning the candidates for women DPRD members for the City of Surabaya in the coming period.